Climbing the Trail to Heaven: Traditional Funerals and Burial Practices in Dane-Zaa Territory-An Ethnographic Account from Northeastern British Columbia - Zuraima Fitriani Salim; Tiarnita Maria Sarjani Br. Siregar; Ami Girsang; Nur Aini Siregar; Sherin Regina Reafflesia Barus (Ravine Publisher, 2025)
The purpose of this research is to investigate two customary funerals conducted by the Dane-zaa First Nation of Northeastern British Columbia, known as the Doig River First Nation. Both funerals included a lot of drumming, singing, and dancing around the fire in keeping with the Dane-zaa custom. Still, there was one key distinction between the two rituals. The funeral held in 2019 for Janice Askoty was a hybrid service that included a Christian liturgy and customary rituals. Such a ritual highlighted the conflicts that already existed among community members over faith and belief systems. There were no conflicts throughout the Christian service that was part of Annie Oker's 2020 funeral. In this paper, the researcher use the notion of syncretism and my observations to illustrate how Christian practices have been merged with indigenous cultural practices, symbols, and beliefs to create new blended practices. Simultaneously, the researcher highlight how certain customs (such as drumming, singing, and dancing around the fire) have endured to this day because they have not been altered by outside forces. Finally, the researcher discuss how the history of colonialism continues to show itself in funerary celebrations and how the community members view, confront, and resist it.